Quantitative Immunomorphological Analysis of Heat Shock Proteins in Thyroid Follicular Adenoma and Carcinoma Tissues Reveals Their Potential for Differential Diagnosis and Points to a Role in Carcinogenesis - Alessandro Pitruzzella; Letizia Paladino; Alessandra Maria Vitale; Stefania Martorana; Calogero Cipolla; Giuseppa Graceffa; Daniela Cabibi; Sabrina David; Alberto Fucarino; Fabio Bucchieri; Francesco Cappello; Everly Conway de Macario; et al. (Applied Sciences, 2019)
Hsp27, Hsp60, Hsp70, and Hsp90 are chaperones that play a crucial role in cellular homeostasis and differentiation, but they may be implicated in carcinogenesis. Follicular neoplasms of the thyroid include follicular adenoma and follicular carcinoma. The former is a very frequent benign encapsulated nodule, whereas the other is a nodule that infiltrates the capsule, blood vessels and the adjacent parenchyma, with a tendency to metastasize. The main objective was to assess the potential of the Hsps in differential diagnosis and carcinogenesis. We quantified by immunohistochemistry Hsp27, Hsp60, Hsp70, and Hsp90 on thin sections of human thyroid tissue with follicular adenoma or follicular carcinoma, comparing the tumor with the adjacent peritumoral tissue. Hsp60, Hsp70, and Hsp90 were increased in follicular carcinoma compared to follicular adenoma, while Hsp27 showed no difference. Histochemical quantification of Hsp60, Hsp70, and Hsp90 allows diagnostic distinction between follicular adenoma and carcinoma, and between tumor and adjacent non-tumoral tissue. The quantitative variations of these chaperones in follicular carcinoma suggest their involvement in tumorigenesis, for instance in processes such as invasion of thyroid parenchyma and metastasization.